Design and Development of a Simple Stirred Tank Photobioreactor for Algal Production (Journal of Solar Energy Research Updates, 2021)
A simple and efficient stirred tank photobioreactor was designed and developed for micro algal culture. The culture system was made of glass and consists of four major parts: culture system container, stirrer, aerator rod and aerator pump. The reactor had proved to be well suited for the cultivation of micro alga Chlorella sp. Two different trials were run for microalgal culture. The lux intensity at the photobioreactor was maintained at 200lux. The algal biomass volumetric output rate was 5.85g l-1 d-1.